(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Introduction: Emergence of multidrug-resistant tuberculosis (MDR-TB) urgently demands for simple, rapid and inexpensive methods of its detection for the effective treatment of drug resistant tuberculosis, particularly in low-income countries. Methodology: This prospective study was carried out at National Tuberculosis Reference Laboratory and South Asian Association of Regional Cooperation (SAARC) Tuberculosis and HIV/AIDS Centre, Thimi, Bhaktapur, Nepal, from November 2009 to May 2010 to evaluate nitrate reductase assay (NRA) efficacy for rapid determination of streptomycin, isoniazid, rifampicin and ethambutol susceptibility of Mycobacterium tuberculosis strains. Results: A total of 113 clinical isolates of M. tuberculosis were tested for four first line antitubercular drugs by nitrate reductase assay and were compared with standard proportion method. Results were available in 7-14 days by NRA as compared to proportion method which generally takes 4-6 weeks. The sensitivity and specificity of NRA were 98.1% and 100% for isoniazid, 95.1% and 98.6% for rifampicin, 91.4% and 94.9% for streptomycin, and 78.6% and 97.9% for ethambutol, respectively. Agreement between NRA and proportion method were 99.1%, 97.3%, 93.8%, 95.6% for isoniazid, rifampicin, streptomycin and ethambutol, respectively. Conclusion: NRA is easier, inexpensive and reliable method for susceptibility testing of Mycobacterum tuberculosis for isoniazid and rifampicin, the two most important drugs for the treatment of tuberculosis. The reduction in susceptibility testing time, and higher sensitivity and specificity of NRA method is of fundamental importance in detecting MDR-TB. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 5-8 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7971